Analysis of the financial feasibility of ship repair service sector companies based on break-even points in surabaya (the case of the planned establishment of pt marine service) - M. Azizul Khakim (Institute of Computer Science (IOCS), 2023)
Surabaya is one of the second largest cities in Indonesia. Geographically Surabaya is in the lowlands and is surrounded by the sea. Surabaya is the entry point for sea expeditions for Eastern Indonesia. Based on the explanation above, the author gives the opinion that Surabaya also has potential in the sea transportation sector. This study aims to provide an overview that business in the field of sea transportation has good potential. This analysis is based on the results of calculating Break Even Points. The author-, provides an overview of his analysis based on a real case of forming a company with services in the field of ship repair in the city of Surabaya. In this case, various facts related to the maritime sector were found, especially in the field of ship repair services. The author has found that new companies can be formed because of market demand, there are interested parties who are aware of the request, and there are supporting roles from various parties such as regulators, society, communities, and so on. One of the interested parties in question is investors. Investor analysis in investing decisions is based on break-even point analysis which can provide an overview of the investment breakeven period of the investor, as well as the risks that the investor may accept.